1991
DOI: 10.1111/1523-1747.ep12465212
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Function of Human Keratinocyte Cultures Grown at the Air-Liquid Interface

Abstract: Stratum corneum (SC), the outermost and least permeable layer of skin, is the major barrier to passive transepidermal water loss. In the research described in this paper, we have used human keratinocyte cultures, grown at the air-liquid (A/L) interface, to examine the relationship between epidermal differentiation (including SC formation) and barrier function. Histologically, the A/L culture showed several markers of complete differentiation, including the presence of well-organized and defined epidermal cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 29 publications
4
46
1
2
Order By: Relevance
“…We also investigated the effect of ARA290 on leukocyte adhesion behavior, which is an important factor of tissue infiltration and/or microvascular injury due to interactions with the vascular endothelium (21). TNF-α and interleukin (IL)-1β are known to induce cell adhesion molecules (CAMs) on the surface of the endothelium and circulating leukocytes along with other actions that cause hypercoagulability (22)(23)(24). Therefore, it is plausible that suppression of the TNF-α-driven response by ARA290 could impact on leukocyte-endothelial adhesion in the wounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the effect of ARA290 on leukocyte adhesion behavior, which is an important factor of tissue infiltration and/or microvascular injury due to interactions with the vascular endothelium (21). TNF-α and interleukin (IL)-1β are known to induce cell adhesion molecules (CAMs) on the surface of the endothelium and circulating leukocytes along with other actions that cause hypercoagulability (22)(23)(24). Therefore, it is plausible that suppression of the TNF-α-driven response by ARA290 could impact on leukocyte-endothelial adhesion in the wounds.…”
Section: Resultsmentioning
confidence: 99%
“…Biopsy punches of 6 mm diameter were taken from the following areas: three from the wound center (>5 mm from edge of wound), three from wound edges (although entirely within the burn wound), and three from healthy skin outside of the wound (>5 mm from wound) at selected time points. At minor time points (4,6,8,12, and 36 h postburn) at least three animals, and at major time points (24,48, and 72 h postburn), at least eight animals were killed to harvest the tissues. Tissues were ground in liquid nitrogen and further processed to obtain supernatants of tissue homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 In vitro human epidermal equivalents (HEEs) that parallel epidermal properties are essential for studying barrier development and function. Although previous HEEs have shown morphological and biochemical similarities to native human skin, their barrier function is reduced compared to in vivo skin, [15][16][17][18][19][20][21] necessitating the addition of fibroblasts or de-epidermized dermis (DED) can result in batch-tobatch variability and increased lead time to developing functionally optimal HEEs. Several parameters have been identified that enhance barrier formation and homeostasis in human and animal models.…”
mentioning
confidence: 99%
“…(Mak et al, 1991;Nolte et al, 1993;Sun et al, 2015) 1.  Compreensão e controle da resposta celular;…”
Section: Redução De Umidadeunclassified
“…Eles puderam observar uma redução na perda de água transepidermal, no entanto, nenhuma alteração morfológica foi notada. Sugere-se que o gradiente de água através das camadas da epiderme tenham uma forte influencia sobre a diferenciação das queratinócitos (Mak et al, 1991). Em estudo semelhante, Nolte e colegas (1992) observaram que ao reduzir à umidade no cultivo dos queratinócitos em relação às culturas controles (de >90% de umidade para cerca de 50-60%) houve uma melhora da função barreira do estrato córneo, apesar de não ter sido observada nenhuma alteração clara na composição e conteúdo Com base nestes questionamentos a cerca da importância da baixa umidade na promoção da diferenciação celular, testamos transferir as peles no 9° dia de cultura da interface ar-líquido para outra incubadora na qual a bandeja de água foi parcialmente recoberta com filme plástico visando a redução na umidade.…”
Section: Padronização Do Equivalente Epidérmicounclassified